Effect of Camellia sinensis, Hypericum perforatum and Urtica dioica on kidney and liver injury induced by carbon tetrachloride in rats - Caglar, Hifa Gulru; Selek, Sahabettin; Koktasoglu, Fatmanur; Koyuncu, Ismail; Demirel, Metin; Sarikaya, Alime; Meydan, Sedat (Cellular and Molecular Biology, 2019)
This study is aimed to investigate the effects of Camellia sinensis (CS), Hypericum perforatum (HP) and Urtica dioica (UD) in kidney and liver injury induced by carbon tetrachloride (CCl4) in rats. Highly toxic CCl4 which is used as a solvent in industry comprises experimental toxicity in rats and is widely used in hepatotoxicity and other tissue injury models. The purpose of this investigation is to monitor blood and various tissues by biochemical and histopathological analysis for preventive effects of CS, HP and UD on oxidative stress induced by administration of CCl4 and to enlighten the probable mechanism. Fifty eight rats were divided into five groups; sham group (Group 1, untreated animals), control CCl4 treated group (Group 2), HP extract-treated group (Group 3), UD extract-treated group (Group 4), CS extract-treated group (Group 5). All rats were anaesthetized at the end of the experiment and the blood was collected from each rat. Afterwards, tissue specimens were obtained. The tissue specimens were immersed in 10% formaldehyde for 24 hours. After routine tissue processing, the liver, kidney and stomach were sectioned in 5µm thickness, stained in hematoxylin and eosin. The histological study was performed by using light microscope. The serum marker enzymes were found to be significantly increased in CCl4–induced liver and kidney damage when compared with the sham group (p<0.05). However, treatment with CS, HP, and UD extracts resulted in decreased activity of serum enzymes. Malondialdehyde (MDA) levels were decreased by 20.51±0.95, 27.98±1.58, and 32.39±3.1 nmol/g wet weight protein in kidney homogenates and 16.65±1.75, 17.22±0.71 and 18.92±71 nmol/g wet weight protein in liver homogenates in CS, HP and UD treated groups, respectively. Our results have shown that additive antioxidants like CS, HP and UD will aid in diminishing these deviations in cases of liver and kidney dysfunction.